Comparison of the Therapeutic Efficacy of Diclofenac Sodium and Methyl Salicylate Phonophoresis in the Management of Knee Osteoarthritis - Sunday AKINBO,; Oluwatoyosi OWOEYE,; Sunday ADESEGUN2, (Archives of Rheumatology, 2011)
Objectives: This study aims to investigate and compare the effectiveness of diclofenac sodium phonophoresis (DSPH), methyl salicylate phonophoresis (MSPH) and conventional therapeutic ultrasound (TUS) in patients with knee osteoarthritis (OA). Patients and methods: Forty-five patients (8 males, 37 females; mean age 57.5 years; range 51 to 64 years) were included in this study between October 2008 and June 2009 and randomly assigned to three groups: DSPH, MSPH and TUS. Ultrasound waves of 1 MHz frequency and 1 watts/cm2 were applied to the target knee with either of two topical pain relieving gels as a coupling medium. Acoustic gel without any active pharmacological agent was applied in the TUS group. Ten treatment sessions were performed in all patients in the three groups. Western Ontario McMaster University Osteoarthritis Index (WOMAC) scores, 20-meter walking time and knee range of motion (ROM) were evaluated before and after the treatment using paired t-test and analysis of variance (ANOVA). Results: The clinical outcome measures improved significantly in the three groups post-treatment (p<0.05). However, patients in the DSPH group had more improvement in all outcome variables compared with the other two groups (p<0.05) except for knee stiffness between DSPH and MSPH (p>0.05). No significant differences were observed in the mean changes in any of the outcome variables between MSPH and TUS therapy (p>0.05). Conclusion: Significant improvements in pain, stiffness, physical function, walking time and knee ROM were attained in all the three groups post-intervention. However, DSPH was found to be more effective compared with the other two groups. The degree of improvement in MSPH and TUS therapy was similar; MSPH was not superior to TUS in patients with knee OA.